Establishing the health and wellbeing needs of mining host community in Brazil, Chile and Peru: a mixed-method approach to identify priority areas for action to help communities meet their SDG3 targets - Brian Rice; Ana Maria Buller; Delia Boccia; Cesar Bazan; Rafael Miranda; Ximena Cea; Rodrigo Laro; Miguel Fontes; Rosalie Hayes; Mariken de Wit; Daniel J. Carter; Alexandra Plowright; et al. (BMC, 2023)
Abstract Background The global mining industry is an important partner in advancing the 2030 Agenda for Sustainable Development. In 2018, Anglo American plc published their Sustainable Mining Plan, containing a goal for improving health and wellbeing aligned with the Sustainable Development Goal 3 (SDG3) targets. Having formed an independent multidisciplinary research consortium, we designed and implemented a mixed-methods approach to attain a deeper understanding of SDG3 priorities within the local context of communities hosting Anglo American mining operations located in Latin America. Methods In 2019, within the host communities of three mining operations in Chile, three in Brazil, and one in Peru, we conducted a qualitative study which included stakeholder workshops and key informant interviews. We also quantitatively appraised existing health data. Findings emerging from the qualitative and quantitative assessments were compared to identify health and wellbeing priority areas for action relevant to each community. Results Across the three countries, 120 people took part in workshops and 35 in interviews. In these workshops and interviews, non-communicable diseases (SDG3.4), harmful alcohol consumption (SDG3.5), and pollution, particularly air pollution (SDG3.9), were consistently identified as areas for priority action. There were similarities in the reporting of individual, interpersonal, community, societal, and structural factors underlying these priority areas across the different communities. The availability of quantitative data was generally good at the state level, becoming increasing sparse as we focused on smaller geographies. The priorities identified in the quantitative assessments generally aligned with those highlighted in the qualitative data. Conclusions We highlight the importance of engaging with local populations to understand and address health needs. To address the priorities identified, intervention packages tailored to the specific needs of host communities, that tackle associated upstream societal level factors, are required. To facilitate this, appropriate monitoring systems and epidemiological investigations should be implemented to better understand the local context and quantify health issues. In the host communities, it is essential for the mining sector to be a key health partner in promoting integrated programmes that contribute to achieving the priority objectives and targets aligned with the SDG3 agenda.